2002
DOI: 10.1182/blood-2002-01-0243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of a natural homozygous Arg67His mutation in the prothrombin gene of a patient with a severe procoagulant defect contrasting with a mild hemorrhagic phenotype

Abstract: In a patient who presented with a severe coagulation deficiency in plasma contrasting with a very mild hemorrhagic diathesis a homozygous Arg67His mutation was identified in the prothrombin gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…The role of proexosite I in substrate recognition is supported further by recent site-directed mutagenesis studies demonstrating that mutation of proexosite I residues in prethrombin 1 (Pre 1) results in loss of factor Va cofactor activity and is correlated with loss of affinity of the proexosite for Hir 54 -65 (SO 3 Ϫ ) (15). A natural mutation of Arg 67 to His in proexosite I of Pro isolated from a patient with a severe procoagulant defect and mild bleeding phenotype also showed reduced factor Va acceleration of its activation (16). In the preceding paper, proexosite I on Pre 1, a Pro analog that lacks the fragment 1 (F1) domain, and Pre 2 was shown to be activated by cleavage of Arg 320 -Ile 321 , generating the active intermediate, meizothrombin des-fragment 1 (MzT(-F1)), and the product, thrombin, respectively.…”
mentioning
confidence: 81%
“…The role of proexosite I in substrate recognition is supported further by recent site-directed mutagenesis studies demonstrating that mutation of proexosite I residues in prethrombin 1 (Pre 1) results in loss of factor Va cofactor activity and is correlated with loss of affinity of the proexosite for Hir 54 -65 (SO 3 Ϫ ) (15). A natural mutation of Arg 67 to His in proexosite I of Pro isolated from a patient with a severe procoagulant defect and mild bleeding phenotype also showed reduced factor Va acceleration of its activation (16). In the preceding paper, proexosite I on Pre 1, a Pro analog that lacks the fragment 1 (F1) domain, and Pre 2 was shown to be activated by cleavage of Arg 320 -Ile 321 , generating the active intermediate, meizothrombin des-fragment 1 (MzT(-F1)), and the product, thrombin, respectively.…”
mentioning
confidence: 81%
“…For example, reagents that block proexosite I such as hirugen and bothrojaracin inhibit macromolecular substrate cleavage by prothrombinase or the FXa-FVa complex (3,20,21). Additionally, proexosite I prethrombin-1 mutants and a naturally occurring prothrombin variant (Arg 67 to His, chymotrypsin numbering system (22)) are poor substrates for prothrombinase and FXa-FVa (23,24). Interestingly, these probes or mutations reduced the rate of IIa generation only in the presence of the cofactor, suggesting a link between FVa and proexosite I.…”
mentioning
confidence: 99%
“…By contrast, this relationship is much more elusive in dysprothrombinemia and could be related to the molecular defect. 1 We report an homozygous mutation in the prothrombin gene (Arg388(73)His, human prothrombin numbering with the chymotrypsinogen numbering of thrombin residues in brackets) and describe its phenotypic expression.…”
Section: A Natural Variant With a Point Mutation Resulting In A Homozmentioning
confidence: 99%
“…8,9 In conclusion, the experimental data showed that both procoagulant and anticoagulant functions of the R388(73)H natural variant are impaired. Akhavan et al 1 have already proposed that substitutions that affect both procoagulant and anticoagulant functions of thrombin might, at least in part, counterbalance each other so that the hemostatic equilibrium is not drastically modified. The very mild bleeding tendency observed in the proband described here gives further support to this hypothesis.…”
Section: A Natural Variant With a Point Mutation Resulting In A Homozmentioning
confidence: 99%